Immune inhibitory receptor agonist therapeutics - Lovewell, Rustin R.; Langermann, Solomon; Flies, Dallas B. (Frontiers in Immunology, 2025)
The immune system maintains the health of an organism through complex sensing and communication mechanisms. Receptors on the surface of immune cells respond to stimuli resulting in activity described at its most basic as inhibitory or stimulatory. Significant progress in therapeutic intervention has occurred by modulating these pathways, yet much remains to be accomplished. Therapeutics that antagonize, or block, immune inhibitory receptor (IIR) pathways, such as checkpoint inhibitors in cancer are a key example. Antagonism of immune stimulatory receptors (ISRs) for dysregulated inflammation and autoimmunity have received significant attention. An alternative strategy is to agonize, or induce signaling, in immune pathways to treat disease. Agonism of ISRs has been employed with some success in disease settings, but agonist therapeutics of IIRs have great, untapped potential. This review discusses and highlights recent advances in pre-clinical and clinical therapeutics designed to agonize IIR pathways to treat diseases. In addition, an understanding of IIR agonists based on activity at a cellular level as either agonist suppression of stimulatory cells (SuSt), or a new concept, agonist suppression of suppressive cells (SuSu) is proposed.